Advancements in Synthesis Strategies and Optoelectronic Applications of Bio-Based Photosensitive Polyimides - Guangning Yu; Qiwen Ma; Hai-Yang Chang; Rongrong Zheng; Cheng Wang; Li-Ying Guo (International Journal of Optics)
With the rapid development of information, energy, and materials industries in China, the demand for high-performance polymers is gradually increasing. Photosensitive polyimide (PSPI) has emerged as an ideal choice for high-performance optoelectronic materials due to its outstanding thermal stability, mechanical strength, and low dielectric constant. In particular, bio-based photosensitive polyimide prepared from bio-based chemicals, as a green polymer material, not only reflects the advantages of environmental protection and resource efficiency but also contributes to carbon neutrality. However, how to improve the photolithography efficiency while maintaining the thermodynamic performance and environmental friendliness and how to balance the pros and cons of low-molecular-weight matrixes are still challenges in the research. This review systematically summarizes the synthesis and performance characteristics of photosensitive polyimides, bio-based polyimide, and bio-based photosensitive polyimides and further explores the future application prospects of bio-based polyimides in the field of high-performance optoelectronic materials.